A study of expanded polyethylene (EPE) pattern application in aluminium lost foam casting - Guler, K. A.; Kisasoz, A.; Karaaslan, A. (PLEIADES PUBLISHING INC, 2015)
The lost foam casting (LFC) process is a kind of casting technique based on using refractory coated polymeric foam patterns and replacing of them by liquid metal during filling. Except limited applications of other kind of foams, expanded polystyrene (EPS) is the most common pattern material of LFC process. It has been used since onset of the method. In this work, expanded polyethylene (EPE) was used as alternative pattern material and compare with EPS by aluminium castings in two different temperatures. Casting experiments were carried out with a well known aluminium alloy A380 at 720A degrees C and 780A degrees C. Porosity contents of the specimens were investigated and compared with density calculations and stereo microscope observations. In brief, EPE can be an alternative pattern material only in right conditions and it is not as useful as EPS. It slows down metal flow and in low casting temperatures EPE causes misrun. Also its decomposition residues contaminate moulding sand.
Keywords: lost foam casting; EPS pattern; EPE pattern; MMA-ST COPOLYMER; MODEL; DEGRADATION; Metallurgy & Metallurgical Engineering